Hazard Analysis of Occupational Health and Safety (OHS) Using The JSA (Job Safety Analysis) Method in Grey Weaving 2 Warehouse PT XYZ - Novianti, Farida; Windriya, Anafil (Asian Journal of Logistics Management, 2023)
PT XYZ is a company engaged in the textile sector with one of its products being grey cloth which is stored in the grey 2 warehouse before being released. In the course of their activities, even though they have implemented Occupational Health and Safety (OHS), workers are still found to be negligent which has the potential to cause work accidents. For this reason, it is necessary to identify the hazards of each job in the grey 2 warehouse using the Job Safety Analysis (JSA) method. The purpose of this study is to determine the potential hazards that exist in each job and determine recommendations for their control. This research uses descriptive qualitative method. Data collection was carried out by observation, interviews, and documentation. The results showed that from all the work carried out in the grey weaving 2 warehouse, there were 18 identified potential hazards. Control recommendations that can be carried out by the company are to use complete Personal Protective Equipment (PPE), focus or not joke when working, ensure the condition of work tools before use, ensure that the path to be passed is safe, put work tools in the right place, arrange cloth tightly, and maintain a safe distance from work tools. Advice that can be given to companies is to provide education about hazards and control recommendations for each job, provide reward to workers, and form an OHS team.